Development of technique for in vitro embryotoxicity of dental biomaterials - Koichi Imai, D.D.S., Ph.D (Elsevier, 2016)
The Embryonic Stem Cell Test (EST) developed in Germany in 1997 is known as a screening test method capable of predicting the presence of unknown chemicals influencing normal human development. Firstly, we investigated the embryotoxicity of 24 types of monomer including dental monomers and dental alloy-component metal elements using this test. Monomers including Bis-GMA contained in base resin of composite resin exhibited weak embryotoxicity, and the toxicity level varied among dental alloy-component metal elements. It was clarified that metal ions eluted from currently sold dental alloys show no embryotoxicity. Then, we investigated a method that also considers human metabolic activity, which is not possible with the EST, in the results of embryotoxicity. In addition, an evaluation method using a hybrid culture system for hepatocytes and mouse ES cells and a method using oviduct or uterus cells for feeder cells were also investigated.